Muscle- and Mode-Specific Responses of the Forearm Flexors to Fatiguing, Concentric Muscle Actions - Ethan Hill; Terry Housh; Cory Smith; Richard Schmidt; Glen Johnson (MDPI AG, 2016)
Background: Electromyographic (EMG) and mechanomyographic (MMG) studies of fatigue have generally utilized maximal isometric or dynamic muscle actions, but sport- and work-related activities involve predominately submaximal movements. Therefore, the purpose of the present investigation was to examine the torque, EMG, and MMG responses as a result of submaximal, concentric, isokinetic, forearm flexion muscle actions. Methods: Twelve men performed concentric peak torque (PT) and isometric PT trials before (pretest) and after (posttest) performing 50 submaximal (65% of concentric PT), concentric, isokinetic (60°·s−1), forearm flexion muscle actions. Surface EMG and MMG signals were simultaneously recorded from the biceps brachii and brachioradialis muscles. Results: The results of the present study indicated similar decreases during both the concentric PT and isometric PT measurements for torque, EMG mean power frequency (MPF), and MMG MPF following the fatiguing workbout, but no changes in EMG amplitude (AMP) or MMG AMP. Conclusions: These findings suggest that decreases in torque as a result of fatiguing, dynamic muscle actions may have been due to the effects of metabolic byproducts on excitation-contraction coupling as indicated by the decreases in EMG MPF and MMG MPF, but lack of changes in EMG AMP and MMG AMP from both the biceps brachii and brachioradialis muscles.